2019
DOI: 10.1002/slct.201803792
|View full text |Cite
|
Sign up to set email alerts
|

A Green Route for Quick and Kilogram Production of Reduced Graphene Oxide and Their Applications at Low Loadings in Epoxy Resins

Abstract: This work reports a green and facile approach to produce bulk amount reduced Graphene Oxide using Graphene Oxide as precursor through Ball Milling in presence of Zinc (Zn) powder activated with NaOH (0.5 ml NaOH (1 M) for 2 g Zn powder). Compared to most of the reported reduction of GO by using hydrazine or any other means, the present route is quite simple, inexpensive and eco-friendly. Since the proposed reduction for GO to rGO involves a solid-state processing assisted with a friction and chemical reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Narayanan et al [25] also reported the hydrothermal synthesis of rGO using starch as reducing agent. The combination of the green chemical reduction with mechanical exfoliation (e.g., Taylor vortex flow or ball milling) is another eco-friendly strategy to synthesize rGO [43,44]. The green reduction of GO is a low-cost process.…”
Section: Green Chemical Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Narayanan et al [25] also reported the hydrothermal synthesis of rGO using starch as reducing agent. The combination of the green chemical reduction with mechanical exfoliation (e.g., Taylor vortex flow or ball milling) is another eco-friendly strategy to synthesize rGO [43,44]. The green reduction of GO is a low-cost process.…”
Section: Green Chemical Reductionmentioning
confidence: 99%
“…Not mentioned rGO (BM/Zn) Epoxy resin/rGO (0.1-0.3%) composites Improvement of thermomechanical properties. [44] rGO: reduced graphene oxide. UV: ultraviolet.…”
Section: Polymer Composites Containing Rgomentioning
confidence: 99%
See 1 more Smart Citation
“…The weak broad peak from 3491 to 2920 cm −1 is due to O-H stretching vibrations in hydroxyl groups present on the basal plane and of intercalated free H 2 O molecules [20]. Residual CO 2 adsorbed on to the sample results in a small peak at 2333 cm −1 [34]. 1403 cm −1 peak is attributed to O-H bending vibrations incurred by the angular deformation of water adsorbed on the sample [32].…”
Section: Resultsmentioning
confidence: 99%